KINERJA KOPERASI PERIKANAN PANTAI MADANI DARI SISI KEUANGAN (Kasus Koperasi di Teluk Pambang, Bengkalis) - M Ramli; Nur’aini ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
Research aims to see cooperation performance from finance, Is theperformance good and Well. Based on finance ratio analysis, Cooperationliquidity value on standard value 125%, Also solvability value on standard value110%. For value rentability value under standard value 10%, Meaning fromcooperation performance rentability aspect not good. Based on heavy value,LSR's value total with heavy still on 100%, Meaning Koperasi Perikanan PantaiMadani (KPPM) still stay in condition wells.